#### Answer

x = $-\frac{2}{3}$

#### Work Step by Step

$\frac{2}{5}x - \frac{1}{12} = -\frac{3}{5}x - \frac{3}{4}$
Add $\frac{3}{5}x$ to both sides:
$\frac{5}{5}x - \frac{1}{12} = -\frac{3}{4}$
x - $\frac{1}{12} = -\frac{3}{4}$
Add $\frac{1}{12}$ to both sides:
x = $-\frac{3}{4} + \frac{1}{12}$
x = $-\frac{9}{12} + \frac{1}{12}$
x = $-\frac{8}{12}$
x = $-\frac{2}{3}$
Check with substitution:
$\frac{2}{5}(-\frac{2}{3}) - \frac{1}{12} = -\frac{3}{5}(-\frac{2}{3}) - \frac{3}{4}$
$-\frac{4}{15} - \frac{1}{12} = \frac{6}{15} - \frac{3}{4}$
$-\frac{1}{12} + \frac{3}{4} = \frac{6}{15} + \frac{4}{15}$
$\frac{8}{12} = \frac{10}{15}$
$\frac{2}{3} = \frac{2}{3}$